2018
DOI: 10.7717/peerj.5353
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of virulent multidrug-resistantEnterococcus faecalisandEnterococcus faeciumin the pigs, farmers and farm environments in Malaysia

Abstract: BackgroundEnterococcus faecalis and Enterococcus faecium are ubiquitous opportunistic pathogens found in the guts of humans and farmed animals. This study aimed to determine the occurrence, antimicrobial resistance, virulence, biofilm-forming ability and genotypes of E. faecalis and E. faecium from swine farms. Correlations between the genotypes, virulotypes, antibiotic resistance, and the environmental factors such as locality of farms and farm hygiene practice were explored.MethodsE. faecalis and E. faecium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…Accordingly, in the current study, 72% of samples were infected with E. faecalis, 10.75% with E. faecium, and 17.25% with other Enterococcus species. Our results showed that among E. faecalis and E. faecium isolates, resistance to cell wall-active antibiotics (vancomycin, teicoplanin, and fosfomycin trometamol) were 33.5% and 53.5%, respectively, which are consistent with its global prevalence (8,40,46). However, among E. faecalis and E. faecium isolates the highest resistance was to fosfomycin trometamol antibiotic (27% and 32%, respectively) while for the other two antibiotics it was almost the same (5.5% and 10%, respectively).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Accordingly, in the current study, 72% of samples were infected with E. faecalis, 10.75% with E. faecium, and 17.25% with other Enterococcus species. Our results showed that among E. faecalis and E. faecium isolates, resistance to cell wall-active antibiotics (vancomycin, teicoplanin, and fosfomycin trometamol) were 33.5% and 53.5%, respectively, which are consistent with its global prevalence (8,40,46). However, among E. faecalis and E. faecium isolates the highest resistance was to fosfomycin trometamol antibiotic (27% and 32%, respectively) while for the other two antibiotics it was almost the same (5.5% and 10%, respectively).…”
Section: Discussionsupporting
confidence: 81%
“…The most common human infectious strains of Enterococcus are E. faecalis (85-90%) and E. faecium (10-15%) leading to urinary tract infections, endocarditis, bacteremia, wound infection, abdominal infections, pelvic infections, and meningitis (4). On the other hand, about 30% of all nosocomial bloodstream infections are associated with Enterococcus species and Staphylococcus aureus, resulting in significant morbidity and mortality (5)(6)(7)(8). Based on the United States Nosocomial Infections Surveillance System's data, Enterococci are considered as one of the nosocomial pathogens (9).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 represents the phylogenetic tree constructed with the entire 28 optrA -carrying E. faecalis genomes using as reference the genome of E. faecalis V583. The healthy humans included correspond to a human volunteer (Efs 599) of the NIH Human Microbiome Project [30] and two swine farmers (Enfs94/P.En218) working in pig farms from Malaysia [23]. In the four E. faecalis genomes from hospitalized patients in China, linezolid resistance was not associated with the consumption of linezolid and an asymptomatic gut colonization was speculated by the authors [25].…”
Section: Resultsmentioning
confidence: 99%
“…no. MJBW01000000) lacked optrA , but as it was included in the same research project (“ Gastrointestinal health of animal handlers with special emphasis on potential zoonotic transmission of bacterial infection ”) of other related optrA -carrying E. faecalis isolated from pigs, we maintained it for comparison [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation